The vulnerability of Palestinian refugees from Syria - Morrison, L (Refugee Studies Centre, University of Oxford, 2014)
While Syrian nationals may eventually return to their home country, the future for Palestinians from Syria is increasingly uncertain. Meanwhile they are more vulnerable, and treated worse, than most other refugees from the Syrian conflict.